Combining ecophysiological models and genetic analysis: a promising way to dissect complex adaptive traits in grapevine - Vivin, Philippe; Lebon, Éric; Dai, ZhanWu; Duchêne, Eric; Marguerit, Elisa; García de Cortázar-Atauri, Iñaki; Zhu, Junqi; Simonneau, Thierry; Van Leeuwen, Cornelis; Delrot, Serge; Ollat, Nathalie (OENO one, 2017)
Designing genotypes with acceptable performance under warmer or drier environments is essential for sustainable crop production in view of climate change. However, this objective is not trivial for grapevine since traits targeted for genetic improvement are complex and result from many interactions and trade-off between various physiological and molecular processes that are controlled by many environmental conditions. Integrative tools can help to understand and unravel these Genotype × Environment interactions. Indeed, models integrating physiological processes and their genetic control have been shown to provide a relevant framework for analyzing genetic diversity of complex traits and enhancing progress in plant breeding for various environments. Here we provide an overview of the work conducted by the French LACCAVE research consortium on this topic. Modeling abiotic stress tolerance and fruit quality in grapevine is a challenging issue, but it will provide the first step to design and test in silico plants better adapted to future issues of viticulture.